Interactive and independent effects of light and noise pollution on sexual signaling in frogs - Smit, Judith A. H.; Cronin, Andrew D.; van der Wiel, Isabelle; Oteman, Bas; Ellers, Jacintha; Halfwerk, Wouter (Frontiers in Ecology and Evolution, 2022)
Urbanization drastically changes environmental conditions, including the introduction of sensory pollutants such as artificial light at night (ALAN) and anthropogenic noise. In order to settle in urban habitats, animals need to cope with this new sensory environment. On a short timescale animals might cope with sensory pollutants via behavioral adjustments, such as changes in sexual signaling, which can have important fitness consequences. While ALAN and anthropogenic noise generally co-occur in urban habitats and are known to be able to interact to modify behavioral responses, few studies have addressed their combined impact. Our aim was, therefore, to assess the effects of ALAN, anthropogenic noise and their interaction on sexual signaling in túngara frogs (Engystomops pustulosus). We observed calling behavior of frogs in urban and forest areas, and subsequently recorded these frogs in a laboratory set-up while independently manipulating light and noise levels. Frogs in urban areas called with a higher call rate and complexity, which was correlated with local sensory conditions. Furthermore, our lab experiment revealed that ALAN can directly alter sexual signaling independently as well as in combination with anthropogenic noise. Exposure to ALAN alone increased call amplitude, whereas a combination of ALAN and anthropogenic noise interacted to lead to a higher call complexity and amplitude. Overall, the response patterns consistently showed that exposure to ALAN and anthropogenic noise led to more conspicuous sexual signals than expected based on the additive effects of single pollutants. Our results support the notion that urban and forest population differences in sexual signaling can be partially explained by exposure to ALAN and anthropogenic noise. Furthermore, by demonstrating interactive effects between light and noise pollution, our study highlights the importance of examining the effects of multisensory pollution, instead of single pollutants, when trying to understand phenotypic divergence in urbanized versus natural areas.